Network Pharmacology Interpretation of Fuzheng–Jiedu Decoction against Colorectal Cancer. (20th February 2021) - Shi, Hongshuo; Tian, Sisheng; Tian, Hu
Abstract : Introduction . Traditional Chinese medicine (TCM) believes that the pathogenic factors of colorectal cancer (CRC) are "deficiency, dampness, stasis, and toxin, " and Fuzheng–Jiedu Decoction (FJD) can resist these factors. In this study, we want to find out the potential targets and pathways of FJD in the treatment of CRC and also explain from a scientific point of view that FJD multidrug combination can resist "deficiency, dampness, stasis, and toxin." Methods . We get the composition of FJD from the TCMSP database and get its potential target. We also get the potential target of colorectal cancer according to the OMIM Database, TTD Database, GeneCards Database, CTD Database, DrugBank Database, and DisGeNET Database. Subsequently, PPI analysis, KEGG pathways analysis, and GO biological processes analysis were carried out for the target of FJD in the therapy of colorectal cancer. In addition, we have also built a relevant network diagram. Results . In this study, we identified four core compounds of FJD in the therapy of colorectal cancer, including quercetin, kaempferol, beta-sitosterol, and stigmasterol. At the same time, we also obtained 30 core targets, including STAT3, INS, TP53, VEGFA, AKT1, TNF, IL6, JUN, EGF, CASP3, MAPK3, MAPK1, MAPK8, SRC, IGF1, CCND1, ESR1, EGFR, PTEN, MTOR, FOS, PTGS2, CXCL8, HRAS, CDH1, BCL2L1, FN1, MMP9, ERBB2, and JAK2. FJD treatment of colorectal cancer mainly involves 112 KEGG pathways, including FoxO (hsa04068) signaling pathway, PI3K-Akt (hsa04151) signaling pathway, HIF-1 (hsa04066) signaling pathway, T cell receptor (hsa04660) signaling pathway, and ErbB (hsa04012) signaling pathway. At the same time, 330 GO biological processes were summarized, including cell proliferation, cell apoptosis, angiogenesis, inflammation, and immune. Conclusions . In this study, we found that FJD can regulate cell proliferation, apoptosis, inflammation and immunity, and angiogenesis through PI3K-Akt signaling pathway to play an anti-CRC effect.